Progress in Understanding the Neurological Basis of Learning Difficulties Through fMRI Studies - Handayani, Fitriah (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2024)
Learning difficulties are conditions where students have difficulty receiving lessons and developing the potential that exists within them. Disabilities in one or more academic areas, such as reading, writing, mathematics, and spelling, as well as more general skills, such as listening, speaking, and thinking, can cause learning difficulties. While FMRI (Functional Magnetic Resonance Imaging) studies are used to study activities the human brain and understanding how the brain functions. This research was conducted with the aim of understanding the neurological basis of learning problems through fMRI studies. Using fMRI, researchers can see changes in brain signals that occur during mental activities, such as learning, and identify areas of the brain that are larger or smaller when processing information. The method used in this research is a quantitative method. This method is a way of collecting numerical data that can be tested. Data was collected through distributing questionnaires addressed to students. Furthermore, the data that has been collected from the results of distributing the questionnaire will be accessible in Excel format which can then be processed using SPSS. From the research results, it can be seen that this research can create better teaching methods and help students who experience learning difficulties improve students' abilities to the maximum, as well as help in developing more effective teaching strategies to improve students' learning abilities. From this study, researchers can conclude that Understanding the Neurological Basis of Learning Difficulties Through MRI Studies can be used to understand how the brain learns and to identify areas of the brain that are more active when processing information, thereby enabling students to learn better.